Crisis management in the sports and school activity department from the viewpoint of workers in the Baghdad Education Directorate, Rusafa 2 - م.د. حيدر علي موسى م.م. مروه خالد خزعل (physical education and sport sciences college for women/ Baghdad University, 2021)
The study aimed to identify the level and manner in which crises are managed from the point of view of workers in the activity section of an athlete in the Baghdad Education Directorate, Rusafa II. The modified questionnaire was distributed to a number of workers in this section who ran as a sample and the questions in it were answered by them As the results of the answers to this questionnaire were addressed using the Social Statistical Package System (SPSS), the researcher concluded that the administrative leaderships in the Sports and School Activity Department have a good degree of application in crisis management from the workers' point of view. The researchers also concluded that the Sports and School Activity Department lacks specialized teams and committees. In discovering and managing crises